Do environmental taxes affect energy consumption and energy intensity? An empirical analysis of OECD countries - Gideon Link Sackitey (Cogent Economics & Finance, 2023)
The use of environmental taxes can encourage a shift toward eco-friendly choices. When used in conjunction with other policy tools available, environmental taxes can help bring about the adjustments needed in order to address our current environmental and climate challenges. Therefore the objective of this study was to examine the impact of environmental taxes on energy consumption and energy intensity using panel data covering the period 1995-2014 from 35 OECD countries. I employed environmental tax to total tax ratio, total energy consumption, and total energy intensity to estimate the relation between energy consumption and environmental taxes. Using the fully modified and dynamic OLS techniques and I showed that environmental taxes have a negative effect on energy consumption and energy intensity in the long run. Furthermore, using the Dumitrescu and Hurlin's panel granger causality test I found a bi-directional long-run causality between environmental taxes and energy consumption and intensity. With regards to the disaggregated effect of environmental taxes, this study found that energy taxes (including CO2 taxes) have a larger effect on energy consumption and energy intensity than pollution and transport taxes. To test for the robustness and sensitivity of my model, I resorted to the total environmental tax to GDP ratio and employed both GMM and quantile regressions. Thus, I concluded that environmental taxes have a significant impact on energy consumption and energy intensity among OECD member countries.
Keywords: 330; energy consumption; energy intensity; energy taxes; Environmental taxes; OECD countries